Penilaian Tingkat Kesehatan Keuangan Berdasarkan Rasio Likuiditas, Solvabilitas, dan Profitabilitas Pada PT. Wilmar Cahaya Indonesia - Amelia Putri Adinda; Isnaini Harahap; Nurlaila (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to assess the financial condition of PT. Wilmar Cahaya Indonesia in the 2019-2023 period based on liquidity, solvency and profitability ratios. The methodology used is quantitative descriptive analysis using secondary data from the company's financial reports. The research results show that although the company's liquidity is said to be liquid, a turnover ratio of more than 500% is considered too high. This indicates inadequate capital utilization. The solvency ratio shows a company's healthy financial position, identifying the company as being able to fulfill its long-term obligations. However, the profitability ratio shows poor financial health with the ratio far below standard, tends to decline, and has low ROA and ROE values. The company's inability to use resources efficiently to generate profits is the cause of this decline. Overall, even though PT Wilmar Cahaya Indonesia is liquid and solvable, its financial health for the 2019-2023 period still needs to be improved, especially in terms of profitability. The analysis shows that to increase profitability, companies must improve the effectiveness of current asset management and maximize resource utilization. This study provides an overview of the company's financial situation and can be used as a reference for future management.